STRATEGI PENINGKATAN MUTU PENDIDIKAN MELALUI IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DAN ANALISIS SWOT DI SD NEGERI 14 PADANGSAMBIAN - Chindytia; Bagus Gede Surya Abadi, Ida; Ketut Mas Ayu Marini Putri, Ni; Kadek Subening Metia Putri, Ni; Ayu Dhyana Paramita, Gusti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of implementing School-Based Management (SBM) in improving the quality of education in elementary schools. Elementary School 14 Padangsambian demonstrates efforts to implement SBM in its management despite various challenges such as limited resources, facilities, and external cooperation. This study aims to analyze the implementation of SBM, identify successes and failures, and formulate strategies for improving education quality based on a SWOT analysis. This study uses a mixed approach (quantitative and qualitative). Data were collected through observation, interviews, and questionnaires. The informant in this study was the school principal. The results show that the implementation of SBM at SDN 14 Padangsambian has been running quite well, marked by independent program management and stakeholder participation. The SWOT analysis indicates that the school has strengths and opportunities in human resources and community support, but faces weaknesses and threats in establishing cooperation and the availability of learning resources.